Substock variation in reproductive traits in North Sea cod (Gadus morhua) - Harrald, Marion; Wright, Peter J.; Neat, Francis C. (Canadian Journal of Fisheries and Aquatic Sciences, 2010)
The North Sea stock of Atlantic cod ( Gadus morhua ) is comprised of a number of subcomponents that differ both genetically and phenotypically. A potential cause for such spatial variability is adaptive divergence, which may be linked to differences in thermal environment and (or) historical fishing pressure. Here we present evidence that spatial variation in maturity–size relationships in the wild has a significant intrinsic component. Using a common-environment experiment on wild-caught juveniles raised through to maturity, we demonstrate that cod from the southern North Sea (SNS) mature at larger sizes than those from the northwestern North Sea (NWNS) despite broadly similar growth rates. Consistent with these experimental results, year-class-specific maturity ogives for recent maturing year classes (1999–2001) suggested that the length at which 50% of females reached maturity was 11 cm greater for SNS than for NWNS cod. Under a common environment, smaller female size at maturity partly reflected higher relative liver weight, with NWNS females having a higher relative liver weight than SNS females. By investigating maturation under controlled conditions, our study provides evidence for life history trade-offs in energy allocation between growth, energy storage, and reproduction that may underlie the spatial variation observed in the field.